The Evaluation of Short- and Long-Term Performance of Cold-Mix Asphalt Patching Materials - Chien-Wei Huang; Tsung-Han Yang; Guan-Bo Lin (Advances in Materials Science and Engineering)
Potholes, one of the major types of distress on pavement surfaces, damage vehicles and are a safety hazard for the travelling public. In order to mitigate the effect of potholes, cold-mix asphalt (CMA) patching materials are commonly used for urgent repair of pavement surfaces before resurfacing can be undertaken. Therefore, the short-term (initial stability) and long-term (in-service durability) performance evaluation of CMA patching materials is necessary. This study conducted several curing conditions in the laboratory to investigate short-term, long-term, and moisture effects on pavement surfaces. Moreover, this study compared the Marshall stability of samples prepared under various compaction conditions. Marshall stability, Cantabro abrasion, and UK wheel tracking tests were conducted to evaluate the performance of CMA patching materials. The results indicated that the Marshall stability of dense-gradation (DG) CMA patching materials was higher than that of open-graded (OG) CMA patching materials and the Marshall stability of OG CMA patching materials was highly influenced by the coarse aggregate proportion. The DG and OG CMA patching materials exhibited comparable abrasion resistance, and the Cantabro abrasion ratio was highly correlated to the estimated asphalt film thickness for the OG CMA patching materials. A moisture indicator (MI) was proposed, and the effect of moisture damage on Marshall stability and Cantabro abrasion ratio was related to the proposed MI. The rutting resistance of the DG CMA patching materials was higher than that of the OG CMA patching materials, which is consistent with the Marshall stability result.